Monitoring the effectiveness of river realignment on the Upper Colorado River, Rocky Mountain National Park - Sparacino, Matthew, author; Rathburn, Sara, advisor; Covino, Tim, committee member; Nelson, Peter, committee member; Ronayne, Mike, committee member (Colorado State University. Libraries, 2017)
A 2003 debris flow introduced 36,000 m3 of sediment into a high-elevation wetland on the Upper Colorado River in Rocky Mountain National Park. In September 2015, Park staff built an earthen diversion dam and realigned a 190 m reach of the Colorado River into its historic thalweg through the center of Lulu City wetland. Initial dimensions of the constructed channel were 1.6 m wide and 0.4 m deep with an average bed slope of 1.9%. Pre- and post-restoration measurements are compared to assess the hydro-geomorphic response to the channel realignment within the adjacent wetland. The constructed diversion berm redistributed at least 48% of river discharge from a pre-realignment, west-side channel, to a central channel, which decreased surface-water groundwater exchange as well as the size of near-stream hyporheic zones and altered sediment transport capacity. A sodium chloride tracer was injected during base-flow and electrical resistivity was used to monitor changes in near-channel hyporheic exchange across the realigned channel for approximately 24 hours following the injection. Pre-and post-realignment electrical resistivity analyses indicate a loss of hyporheic exchange in the northern wetland, likely a result of decreased river complexity. Tracer mass balances derived from concurrent surface conductivity measurements indicate increases in solute retention throughout Lulu City wetland, possibly due to increased overbank flow. These results imply that solute retention can increase without an equal increase in hyporheic exchange. Furthermore, local incision greater than 0.5 m, widening of 0.2 to 1 m, and upstream knickpoint migration within the realigned channel during 2016 runoff indicate increases in erosion and local sediment transport. The growth of gravel bars upstream of the diversion berm indicate increased sediment deposition at the head of Lulu City wetland. Results from one year of post-realignment monitoring suggest that the channel realignment has had small-scale effects on hyporheic exchange, solute retention, and sediment transport capacity, with potentially negative consequences for the ecosystem services provided by river-wetland systems. Long-term monitoring and increased instrumentation are required to predict how these changes may be amplified in a larger restoration attempt.